A Prospective Study on the Accuracy of Glycated Albumin in Diagnosing Pregnancies Complicated with Gestational Diabetes Mellitus - Saleem, Hira; Iftikhar, Ghazala; Nazeer, Rabia; Fiaz, Huma; Taj, Nergis; Brohi, Sumera; Depar, Ramsha; Ahmad, Huma (Journal of Neonatal Surgery, 2025)
Background: Gestational diabetes mellitus (GDM) remains to be among the commonest challenge faced during pregnancy and it is of great risk to maternal and the fetus. ‘Although GDM is generally diagnosed using an oral glucose tolerance test (OGTT) not without some drawbacks including inconvenience and low reproducibility there is a growing diabetes gap’. The necessity for alternative biomarkers is evident. Emerging evidence suggests that glycated albumin (GA), which monitors short-term diabetes management, may be helpful in predicting GDM much earlier. This study seeks to evaluate the diagnostic accuracy of GA in comparison with the OGTT and assess its performance against primary GDM screening. Methods: This study recruited 81 pregnant women who were between 20 to 28 weeks of gestation. The participants performed ‘standard glucose tolerance tests for the diagnosis of gestational diabetes along with simultaneous testing for albumin glycation’. GA’s diagnostic performance was assessed by calculating sensitivity, specificity, and area under the ROC curve (AUC). Results: GA levels were significantly higher in the GDM group compared to non-GDM participants (15.3% vs. 12.1%, p < 0.001). GA demonstrated high diagnostic accuracy with a sensitivity of 85.7%, specificity of 84.6%, and an AUC of 0.89. Elevated GA values were also associated with higher neonatal birth weights and increased rates of cesarean delivery. Conclusion: Glycated albumin has substantial promise as an alternative or adjunct diagnostic marker for GDM. Its use is particularly beneficial in clinics where OGTT is impractical due to high precision, shorter timeframes of detection, and ease of testing.